Pengaruh Compesantion dan Job Satisfaction Terhadap Employee Performance dimediasi Employee Engagement pada Bank Swasta di Jakarta - Antonius David Kristanto; Erny Tajib (Glosains: Jurnal Sains Global Indonesia, 2023)
This study aims to determine the effect of compensation and job satisfaction on employee performance mediated by employee engagement in the banking industry. The problems in this study are as follows: (1) Does compensation have an effect on employee performance? (2) Does job satisfaction have an influence on employee performance? (3) Does compensation have an influence on employee performance mediated by Employee Engagement? (4) Does job satisfaction have an influence on employee performance mediated by employee engagement? The sampling method used was purposive sampling method (bank employees) with a total sample of 165 respondents and 19 questions asked. The results of this study indicate that there is no effect of compensation on employee performance. In addition, there is a significant effect of job satisfaction on employee performance. The results of this study also show that there is an influence of compensation on employee performance which is mediated by Employee Engagement and there is also an effect of job satisfaction on employee performance which is mediated by employee engagement.